Strategi Pengembangan Kompetensi Guru Pendidikan Agama Islam dalam Meningkatkan Kualitas Sumber Daya Manusia di Sekolah - Dadan Mardani; Iis Susiawati; Muhammad Faiz Alhaq (YASIN, 2026)
Human resource (HR) policies in education play a strategic role in ensuring the quality and equity of national education; however, their implementation across different levels of governance still shows disparities that need to be systematically examined. This study aimed to analyze the forms, challenges, and strengthening strategies of education HR policies implemented at the national, regional, and institutional levels. A qualitative approach was employed through a literature study and policy analysis of official government documents, institutional reports, and relevant academic literature. The findings show that national policies such as teacher certification, curriculum reform, and training delivered through digital platforms have provided direction for the development of education human resources, but their implementation remains uneven. There are significant differences in teacher certification rates, access to professional development, and teacher distribution, particularly between urban areas and disadvantaged, frontier, and outermost (3T) regions. At regional and institutional levels, limited managerial capacity, budgetary disparities, and weak coordination across policy levels contribute to the low effectiveness of implementation. The study concludes that education HR policies are not yet fully integrated or equitable, thus requiring strengthening in both design and implementation. The implications highlight the importance of data-driven planning, the expansion of digital-based teacher training, enhanced cross-stakeholder collaboration, and the application of performance-based incentive systems to improve the quality and sustainability of education HR policies.